Estimation du besoin en eau des cultures et évapotranspirationderéférenceparlebiaisdulogiciel CROPWAT 8.0 (cultures despommes de terre dans la région de Mascara) - BOUKELLALRachida (My University, 2025)
Efficientmanagementofirrigationwaterrequiresathoroughunderstandingofcropwater needs, in order to betteraligndemandwithavailablesupply in the Wilaya of Mascara. To achievethis, the CROPWAT 8.0 software (Windows version) wasemployed. Afterentering the climatic data (2010–2022), evaporationlevels and irrigation water requirements for potatocropswereassessed. The software generated irrigation schedules and tables thataccuratelydescribe the crop’s water requirements and referenceevapotranspiration, takingintoaccountsoil, climatic, and plant characteristics. Finally, a comparisonwascarried out between the monthly and annual results for the same crop.
Keywords: ETo; ETc; CROPWAT8.0; potato; Mascara